Selective strain-promoted azide–alkyne cycloadditions through transient protection of bicyclo[6.1.0]nonynes with silver or gold. Issue 68 (27th July 2020) - Adachi, Keisuke; Meguro, Tomohiro; Sakata, Yuki; Igawa, Kazunobu; Tomooka, Katsuhiko; Hosoya, Takamitsu; Yoshida, Suguru
Abstract : Complexation of bicyclo[6.1.0]nonynes (BCNs) with silver or gold results in protection from a click reaction with azides. The protection enables selective strain-promoted azide–alkyne cycloadditions of diynes keeping the BCN moiety unreacted. Abstract : Complexation of bicyclo[6.1.0]nonynes with a cationic silver or gold salt results in protection from a click reaction with azides. The cycloalkyne protection using the silver or gold salt enables selective strain-promoted azide–alkyne cycloadditions of diynes keeping the bicyclo[6.1.0]nonyne moiety unreacted.